Semantic Development of Prayer in the Quran - Azam Parcham; Mastaneh Abutorabiyan (آموزه‌های قرآنی, 2012)
This article seeks to explain the semantic position of “pray” in a descriptive way in the Quran. Descriptive semantics reviews the relation of term “pray” with the relevant words in the Quran. There is semantic relation between “pray” and the application of the revealed of words such as seek, call, implore, supplicate, worship, seeking forgiveness and… . One of the important conclusions drawn from the semantic fields of prayer is revealing the deep semantic connection of the pray with the other words of the same field in the Quran. These nexus made the term pray influenced completely under the adjacent words and the semantic system available in the Quran. Exploring these nexus and clearing the semantic development of the pray, this article deals with the evolutionary process of man as a semantic approach in accordance with its degrees.